2017
DOI: 10.1111/jsr.12587
|View full text |Cite
|
Sign up to set email alerts
|

The Perception and Attention Functions test battery as a measure of neurocognitive impairment in patients with suspected central disorders of hypersomnolence

Abstract: The aim of the current study was to evaluate an attention test as a discriminative tool to measure neurocognitive impairment in patients with disorders of hypersomnolence. Chronic excessive daytime sleepiness is the main symptom in central disorders of hypersomnolence. For diagnostic purposes and treatment evaluation, reliable assessment of excessive daytime sleepiness is required. Thirty-six patients with central disorders of hypersomnolence were compared with 20 healthy controls. All participants performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Thirty-five studies (73%) assessed a sample of untreated (either drug-naive or drug-free) CDH patients, 10 (21%) assessed a mixed sample of treated and untreated patients and three studies (6%) assessed patients under stable pharmacological treatment. Since Raam's study reported on a mixed population (NT2/IH), we decided to include this study in the IH section being the sample mostly composed by IH patients (10/13 were IH) [7].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-five studies (73%) assessed a sample of untreated (either drug-naive or drug-free) CDH patients, 10 (21%) assessed a mixed sample of treated and untreated patients and three studies (6%) assessed patients under stable pharmacological treatment. Since Raam's study reported on a mixed population (NT2/IH), we decided to include this study in the IH section being the sample mostly composed by IH patients (10/13 were IH) [7].…”
Section: Methodsmentioning
confidence: 99%
“…Three studies used the d2 attention test. Naumann and Zamarian showed that NT1 patients processed fewer items compared to controls; Zamarian also reported increased errors in patients compared to controls [10,17] In the first study, the authors found more lapses in NT1 patients than in controls, but no difference emerged with IH patients and subjective EDS [7]. In the second study, the authors reported increased errors in NT1 patients compared to controls [19].…”
Section: Selective Attentionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fifteen patients suffering from IH were consecutively recruited from the Department of Neurology, Division of Sleep Medicine and Neuromuscular Diseases at the University Hospital Muenster. Diagnosis was made according to standard criteria of the ICSD-3 ( 1 ) as described recently ( 23 ). The Epworth Sleepiness Score (ESS) to assess subjective daytime sleepiness ( 24 ) had to be above 10 and the Horne-Ostberg (HO) score was evaluated by the self-assessment HO questionnaire ( 25 ).…”
Section: Methodsmentioning
confidence: 99%